Non‐linear compact model for FinFETs output characteristics. Issue 8 (14th November 2019) - Ahmed, Umer F.; Ahmed, Muhammad Mansoor; Memon, Qamar D.
Abstract : In this study, a non‐linear compact model for I – V characteristics of FinFETs is presented. The model is developed using the profile of drifting carriers, which plays an important role in determining the device characteristics. A mobility model which incorporates the effect of applied potentials is developed and is used to predict the I – V response of the device. Particle swarm parameter extraction technique is engaged for optimum model applications. It is demonstrated by using the experimental data reported in the literature, that the proposed model can predict the I – V characteristics of FinFETs fabricated using Si and GaN materials having gate lengths ranging from 0.05 to 1 μm.